John Steinbeck and Bo Beskow in the Plaza Del Salvador, Seville, Spain (Spain; Seville, 2022)
John Steinbeck and Bo Beskow sit at a cafe' in the Plaza Del Salvador, Seville, Spain. Plaza del Salvador is located in the quarter of Alfalfa and the district of the Old Town of Seville, and takes its name from the Salvador church, a Mannerist work from the 17th century that is the second biggest church in the city after the cathedral. Original in safe.